ARTIFICIAL INTELLIGENCE RESEARCH TRENDS IN EDUCATION: BIBLIOMETRIC ANALYSIS USING BIBLIOSHINY: TREN RISET ARTIFICIAL INTELLIGENCE DALAM PENDIDIKAN: ANALISIS BIBLIOMETRIK MENGGUNAKAN BIBLIOSHINY - Murni, Odela Priscilia; Dewi, Elsa Nora Ariesta; Afandi, Afandi (EDUCATE, 2024)
ICT which is growing rapidly in the digital era has succeeded in creating an artificial intelligence called Artificial Intelligence for the benefit of various fields of life, especially education. The purpose of this study is to see the development of research on the topic of Artificial Intelligence trends in bibliometric-based education. This research method is using bibliometric methods regarding the production, growth, maturation, and consumption of scientific publications with a descriptive approach using data derived from Scopus regarding Artificial Intelligence in education published in various academic journals, books, patents, proceedings, and so on from 1999 to 2024. The results of this study, namely bibliometric analysis based on Scopus data with 1646 documents on Artificial Intelligence in education, have provided a comprehensive view of the current domain status. The results of the analysis of 21 aspects contained in the overall Scopus data have provided new findings about  Artificial Intelligence in education including: Artificial Intelligence in education gave rise to the words augmented reality, student, and  learning systems which continues to evolve along with the emergence of new research words or themes and the growing popularity of certain topics; It finds many of the studies that are frequently cited, and several articles, authors, and journals play an important role in it. This means that Artificial Intelligence in education today is very dynamic with a steady growth of publications.